Berberine and Its Metabolites: Relationship between Physicochemical Properties and Plasma Levels after Administration to Human Subjects - Spinozzi, Silvia; Colliva, Carolina; Camborata, Cecilia; Roberti, Marinella; Ianni, Cristina; Neri, Flavia; Calvarese, Claudio; Lisotti, Andrea; Mazzella, Giuseppe; Roda, Aldo (Journal of natural products (Washington, D.C.), 2014)
Berberine (1) is an alkaloid used widely in the treatment of several diseases. However, its physicochemical properties, pharmacokinetics, and metabolism remain unclear, and conflicting data have been reported. In this study, the main physicochemical properties of 1 and its metabolites were evaluated, including lipophilicity, solubility, pK a, and albumin binding. A sensitive HPLC-ESIMS/MS method was developed and validated to identify 1 and its main metabolites in human plasma. This method was used to quantify their levels in the plasma of healthy volunteers and hypercholesterolemic patients following a single dose and chronic administration, respectively. In both cases, berberrubine (2) was found to be the main metabolite. Surprisingly, 2 is more lipophilic than 1, which suggests that this compound tautomerizes to a highly conjugated, electroneutral quinoid structure. This was confirmed by NMR studies. These results indicate that the higher plasma concentration of 2 was a consequence of a more efficient intestinal absorption, suggesting that berberrubine is potentially more pharmacologically active than berberine.